ӨЗБЕКСТАННЫҢ ТУНҒЫШ ПРОФЕССОРЫ - Сейтмуратов, Қ. (ILIM hám JÁMIYET, 2023)
The article deals with the issues of Jadid and educational activities and pedagogical thoughts of the prominent Uzbek teacher and poet Abdirauf Fitrat.